80 GHz waveform generated by the optical Fourier synthesis of four spectral sidebands. (7th December 2015) - Fatome, Julien; Hammani, Kamal; Kibler, Bertrand; Finot, Christophe
Abstract: Using the linear phase shaping of a simple four-line optical frequency comb, we experimentally demonstrate the generation of various optical waveforms such as parabolic, triangular or flat-top pulse trains at a repetition rate of 80 GHz. The initial 80 GHz comb is obtained through the nonlinear spectral broadening of a 40 GHz carrier-suppressed sinusoidal beating in a highly nonlinear fiber. Proof-of-principle experiments are reported for two distinct configurations of the waveform generated: continuous trains and bunches of shaped pulses.